Discovery learning with biology practicum to improve student learning activities - Puspitasari, Diana Juliarti; Iriani, Lita; Laenggeng, Abd. Hakim (Universitas Negeri Padang, 2023)
This study aims to apply the discovery learning model with practicum to improve students' learning activities. This is a Classroom Action Research conducted in two cycles. Each cycle consists of planning, implementation, observation and reflection stages. The subjects of this study were students of SMA Negeri 1 Palu with a total of 35 students. Data collection was carried out using student learning activity observation sheets. Based on the results of the study, it can be concluded that the learning activities of students increased from 67.88% or in the sufficient category in cycle I to 84.23% in cycle II or in the very good category. The results of this study indicate that the application of the discovery learning model with practicum can increase student learning activities in biology subjects.